EFFECT OF COMPETENCY AND COMPENSATION ON EMPLOYEE ENGAGEMENT AND THEIR IMPACT ON PERFORMANCE OF ORGANIC EMPLOYEES PT PELABUHAN INDONESIA IV (PERSERO) SAMARINDA BRANCH - Ella Fitria Rahmayani; Adietya Arie Hetami; Muhammad Fikry Aransyah (UIN Sunan Kalijaga, 2021)
This study aims to determine the effect of competence and compensation on employee engagement and their impact on employee performance. Competence is an essential thing that must be considered in managing human resources in the company because competence means a person's ability to do a job based on skills or expertise to produce good results. This research was conducted at PT Pelabuhan Indonesia IV, a State-Owned Enterprise (BUMN) engaged in managing seaports and sea services. The type of research used is descriptive research with a quantitative approach. The sample used is 69 respondents who are Organic Employees of PT Pelabuhan Indonesia IV (Persero) Samarinda branch by using a sample using Nonprobability sampling with the Quota Sampling method with the data analysis technique used is path analysis. The results showed that the competence variable partially had a significant effect on employee engagement, the compensation variable partially had a significant effect on employee engagement, the competence variable partially had a significant effect on employee performance, the compensation variable partially had a significant effect on employee performance, the employee engagement variable partially had an effect significant to employee performance. PT Pelabuhan Indonesia IV (Persero) Samarinda branch is expected to maintain the quality of employees based on competence and expertise in their fields respectively to improve performance as expected by the company. Superiors can also maintain relationships with employees by providing training, advice, and evaluating employee work results to improve employee performance effectively. Furthermore, the company can maintain a system of providing compensation and benefits received by employees to increase employee work loyalty to improve the quality of performance to the company.